Description and phylogenetic relationships of a new, purple-flowered, endangered Schomburgkia (Laeliinae; Orchidaceae) from north-eastern Brazil - Pessoa, Edlley M.; Brito, Vinícius; Ralf-Neto, Fraterno; Fernandes, Geysla; Gomes, Gustavo; Fraga, Elmary; Barros, Maria Claudene (Phytotaxa, 2022)
We describe a new species of Schomburgkia, S. vandenbergiana, from north-eastern Brazil and provide a phylogenetic analysis and a summary of its conservation status. Our phylogenetic analyses indicate that S. vandenbergiana is most likely related to S. undulata and S. gloriosa. The species with dark purple flowers, S. elata, S. splendida, S. undulata and S. vandenbergiana, did not form a clade, and this trait seems to have multiple independent origins. Based on small flower size and number of keels on the disc of the lip, the new species is morphologically more similar to S. heidii, a species native to Colombia and Venezuela, but it differs in the shorter sepals and lip and erose clinandrium margin. The new species should be classified as endangered (EN) based on the IUCN criteria B1ab(i)+2ab(ii).